HUBUNGAN BUDAYA ORGANISASI DAN KEPERCAYAAN PEGAWAI TERHADAP KOMITMEN KARYAWAN TERHADAP STMIK PRINGSEWU - -, Fauzi (Jurnal Manajemen dan Keuangan, 2012)
The aim of this research is to obtain information related to the effect of the organizational culture, and employeeâs trust on organizational commitment. Survey was conducted in this research with 100 sample of employeeâs selected randomly. Data have been analyzed by path analysis.The findings of this research show that employeeâs trust is affected directly organizational culture as well as leadership style. Organizational commitment is affected directly by organizational culture, and as well as employeeâs trust. Based on those findings it can be concluded that any concern toward, organizational culture, and employeeâs trust of STMIK of Pringsewu have an effect on organizational commitment. Therefore, organizational cultur, and employeeâs trust should be put into strategic planning of human resources development in increasing the organizational commitment of STMIK of Pringsewu, however other variables are necessary to be taken into account properly.Keywords : Organizational Culture, Employeeâs Trust, and Organizational Commitment